1991
DOI: 10.1128/jcm.29.1.212-214.1991
|View full text |Cite
|
Sign up to set email alerts
|

Detection of bluetongue virus by using bovine endothelial cells and embryonated chicken eggs

Abstract: Two systems, inoculation of bovine endothelial cells and of embryonated chicken eggs, were compared for detection of bluetongue virus (BTV) in blood specimens from experimentally inoculated sheep. For all BTV serotypes tested, embryonated chicken eggs detected longer periods of viremia than did bovine endothelial cells, primarily by detecting BTV in samples containing lower virus concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 4 publications
(4 reference statements)
0
8
0
Order By: Relevance
“…Intravenous route is widely used and 100–1000 times more sensitive than yolk sac route (Pearson et al. 1985 ; Wechsler and Luedke 1991 ; Clavijo et al. 2000 ; Dadhich 2004 ).…”
Section: Laboratory Diagnosis Of Btmentioning
confidence: 99%
See 3 more Smart Citations
“…Intravenous route is widely used and 100–1000 times more sensitive than yolk sac route (Pearson et al. 1985 ; Wechsler and Luedke 1991 ; Clavijo et al. 2000 ; Dadhich 2004 ).…”
Section: Laboratory Diagnosis Of Btmentioning
confidence: 99%
“…Baby hamster kidney-21 (BHK-21), African green monkey (Vero) and mouse L cell lines are commonly used for growth and maintenance of BTV. Wechsler and Luedke ( 1991 ) had successfully propagated the BTV in calf pulmonary artery endothelial (CPAE) cell lines. They also reported that CPAE was more sensitive than 13 other cell lines.…”
Section: Laboratory Diagnosis Of Btmentioning
confidence: 99%
See 2 more Smart Citations
“…Blood was used for the first round of virus isolation in 10-to 12-day-old chicken embryos, according to the protocol described by Clavijo et al (29). The inoculation of embryonating chicken eggs is more sensitive than cell culture, allowing detection of BTV in samples containing a low viral concentration (30). The blood (1/10 dilution) was intravenously inoculated into an embryo vein, incubated at 33.5 ± 0.5 • C, and monitored daily for 7 days.…”
Section: Virus Isolationmentioning
confidence: 99%